O Mundo fantástico da literatura infantil: a importância do incentivo à leitura na infância para formação de futuros leitores. - CRUZ, Marcia Mônica Bomfim (2023)
It aims to analyze how the fantastic world of children's literature can contribute to the formation of future readers. It presents a methodology with a qualitative approach with an exploratory characteristic. It shows the benefits that children's literature brings to childhood and how much it helps the child to grow as a thinking adult capable of questioning and understanding the reality in which he is inserted. It points out the role of the librarian as a reading mediator and reader trainer, with the child user, aiming to awaken curiosity, pleasure and interest in reading.